The need to harmonise environmental sustainability assessments for pharmaceuticals - Caroline T.A. Moermond; Fiona Adshead; Stefan Berggren; Thea Skafte Böttcher; Marco Cinelli; Ruben de Moor; Yasmin de Wit; Mira Dysgård; Dirk Halet; Arne Hein; Katharina Högdin; Aline Katzenberger; et al. (Sustainable Chemistry and Pharmacy, 2026)

Effect of dissolved versus total zinc levels on bacterial zinc-dependent meropenem co-resistance in River Tyne sediments - Catherine L. Hands; Sonia Gupta; Anke Neumann; Charles W. Knapp; S.Z. Ahammad; Jason Snape; David W. Graham (Environmental Pollution, 2026)

Corrigendum to < Dawning of a new ERA: Environmental Risk Assessment of antibiotics and their potential to select for antimicrobial resistance’> <[Water Research 200 (2021) 117–233]> - Aimee K. Murray; Isobel Stanton; William H. Gaze; Jason Snape (Water Research, 2024)

Basin-wide estimates of loggerhead turtle abundance in the Mediterranean Sea derived from line transect surveys - Andrew DiMatteo; Ana Cañadas; Jason Roberts; Laura Sparks; Simone Panigada; Olivier Boisseau; Anna Moscrop; Caterina Maria Fortuna; Giancarlo Lauriano; Draško Holcer; Hélène Peltier; Vincent Ridoux; et al. (Frontiers in Marine Science, 2022)
Loggerhead turtles are a globally vulnerable species of marine turtle. Broad-scale patterns of distribution and abundance can provide regional managers a tool to effectively conserve and manage this species at basin and sub-basin scales. In this study, combined aerial and shipboard line transect survey data collected between 2003 and 2018 were used to estimate distribution and abundance throughout the Mediterranean Sea. Approximately 230,000 linear kilometers of survey effort, from seven different surveying organizations were incorporated into a generalized additive model to relate loggerhead density on survey segments to environmental conditions. Two spatial density models estimating loggerhead density, abundance, and distribution were generated – one a long-term annual average covering 2003-2018 and another covering the summer of 2018, when a basin-wide aerial survey, the Agreement on the Conservation of Cetaceans of the Black Sea, Mediterranean Sea and Contiguous Atlantic Area Survey Initiative, was performed. Both models were adjusted for availability bias using dive data from loggerhead turtles tagged with time depth recorders. Mean abundance for the long-term average model was estimated as 1,201,845 (CV=0.22). The summer 2018 abundance estimate was 789,244 turtles and covered a smaller area than the long-term average. These estimates represent the first basin-wide estimates of abundance for loggerhead turtles in the Mediterranean not based on demographic models. Both models predicted similar distributions, with higher abundance predicted in the northern Adriatic Sea, central Mediterranean basin, Tyrrhenian Sea, and south of the Balearic Islands. Lower densities were predicted in the eastern Mediterranean Sea and the Aegean Sea. The highest density areas generally did not coincide with previously established adult loggerhead turtle foraging areas, which are typically neritic, indicating the models are predominantly predicting oceanic distributions, where most of the survey effort occurred. Juvenile loggerhead turtles are predominantly oceanic and comprise most of the population, but care must be taken when using these models as they may not accurately predict distribution of neritic foraging areas, where subadult and adult loggerheads can often be found. Despite this limitation, these models represent a major step forward for conservation planning and understanding basin-wide distribution and abundance patterns of this species.

Processes of distribution of pharmaceuticals in surface freshwaters: implications for risk assessment - Simone Bagnis; Mark F. Fitzsimons; Jason Snape; Alan Tappin; Sean Comber (Environmental Chemistry Letters, 2018)

Standard inocula preparations reduce the bacterial diversity and reliability of regulatory biodegradation tests - Andrew K. Goodhead; Ian M. Head; Jason R. Snape; Russell J. Davenport (Environmental Science and Pollution Research, 2014)